2011
DOI: 10.1016/j.seares.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytoplankton and temperature on the reproduction of the Pacific oyster Crassostrea gigas: Investigation through DEB theory

Abstract: DEB theory can be used to obtain a detailed description of energy allocation in organisms and the control of this allocation by temperature and food concentration. In this study, we modified the model of Bourlès et al. (2009) developed for the Pacific oyster, Crassostrea gigas, to improve the description of reproductive effort. The model was amended in two ways: a new set of parameters was incorporated and a full description of gonad construction in spring was added, with a new state variable. The application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 58 publications
(81 reference statements)
2
60
0
Order By: Relevance
“…Handå et al, 2011;Filgueira et al, 2011;Maar et al, 2009;Rosland et al, 2009Rosland et al, , 2011Saraiva et al, 2011a;Thomas et al, 2011;van der Veer et al, 2006), Crassostrea gigas (e.g. Alunno-Bruscia et al, 2011;Barillé et al, 2011;Bernard et al, 2011;Bourlès et al, 2009;Emmery et al, 2011), and other species. Several authors have dynamically coupled DEB models with biogeochemical models to provide feedbacks from aquaculture farms to phytoplankton and nutrient dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Handå et al, 2011;Filgueira et al, 2011;Maar et al, 2009;Rosland et al, 2009Rosland et al, , 2011Saraiva et al, 2011a;Thomas et al, 2011;van der Veer et al, 2006), Crassostrea gigas (e.g. Alunno-Bruscia et al, 2011;Barillé et al, 2011;Bernard et al, 2011;Bourlès et al, 2009;Emmery et al, 2011), and other species. Several authors have dynamically coupled DEB models with biogeochemical models to provide feedbacks from aquaculture farms to phytoplankton and nutrient dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…On examining the median part of the visceral mass, Royer et al (2008) found the percentage surface occupied by the gonad to be directly linked to the number and/or size of gametes produced and therefore representative of reproductive effort, which is linked to the proportion of energy allocated to reproduction (Todd and Havenhand, 1983;Normand et al, 2009). In the DEB theory, oyster reproductive effort was found to depend mostly on the halfsaturation coefficient for ingestion (Bernard et al, 2011). This environment-specific coefficient reflects quantitative and qualitative variability in the oysters' food (Alunno-Bruscia et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The DEB model describes four state variable dynamics: the energy stored in reserves, E, the energy allocated for structural growth, E V , the energy allocated to development and reproduction, E R , and the energy used in the construction of gametes, E GO (see Bernard et al, 2011 for full description). In the DEB model, a constant fraction, κ, of the energy mobilized from the reserves is allocated to growth and structural maintenance, the remainder (i.e.…”
Section: Deb Model Simulationsmentioning
confidence: 99%
See 2 more Smart Citations